Popular cults and religions in Latin America: Identities between tradition and globalization - Parker Gumucio, Christian (1998)
One of the central characteristics of the social change that we are experiencing at the gates of the third millennium has been conceptualized under the term globalization. This is a plurivocal and polysemic term to refer to a complex process by which the diffusion of a new technological paradigm is understood, at the same time as changes in production processes, financial movements, labor markets, organizational and management designs, education , information and communications systems, urban and family lifestyles, consumption patterns, advertising and marketing, knowledge, values ​​and citizen preferences and, therefore, ways of life of societies and people (Tomassini, 1995).